UPAYA KURATOR DALAM MEMAKSIMALKAN ASET HKI MILIK PERSEROAN TERBATAS YANG MENGALAMI PAILIT ATAU PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG - Wibowo, Bintang Herlambang; Griadhi, Ni Made Ari Yuliartini (Kertha Negara : Journal Ilmu Hukum, 2024)
The aim of this research is to determine the involvement of curators in the liquidation and administration of intellectual property assets during times of bankruptcy and PKPU, as well as exploring strategies for optimizing the value of intellectual property assets in these conditions. The research methodology used in this research is normative juridical legal research, which focuses on the analysis of currently applicable legal provisions, namely Law Number 37 of 2004 concerning Bankruptcy and Extension of Debt Payment Obligations, as well as Law Number 40 of 2007 concerning Limited Liability Companies. The results show that the curator fulfills many responsibilities, including the implementation of administrative tasks, management of bankruptcy assets, and supervision and resolution of intellectual property assets. Curators face challenges in effectively using intellectual property assets, especially those that have not been officially registered. To optimize intellectual property (IP) assets, managers have the ability to negotiate with external parties or internal creditors to secure payments and additional company capital. They can also carry out corporate restructuring actions such as mergers, acquisitions, or consolidation, as well as asset liquidation.